Hidden Microatelectases Increase Vulnerability to Ventilation-Induced Lung Injury - Albert, Karolin; Krischer, Jeanne-Marie; Pfaffenroth, Alexander; Wilde, Sabrina; Lopez-Rodriguez, Elena; Braun, Armin; Smith, Bradford J.; Knudsen, Lars (Frontiers in Physiology, 2020)
Mechanical ventilation of lungs suffering from microatelectases may trigger the development of acute lung injury (ALI). Direct lung injury by bleomycin results in surfactant dysfunction and microatelectases at day 1 while tissue elastance and oxygenation remain normal. Computational simulations of alveolar micromechanics 1-day post-bleomycin predict persisting microatelectases throughout the respiratory cycle and increased alveolar strain during low positive end-expiratory pressure (PEEP) ventilation. As such, we hypothesize that mechanical ventilation in presence of microatelectases, which occur at low but not at higher PEEP, aggravates and unmasks ALI in the bleomycin injury model. Rats were randomized and challenged with bleomycin (B) or not (H = healthy). One day after bleomycin instillation the animals were ventilated for 3 h with PEEP 1 (PEEP1) or 5 cmH2O (PEEP5) and a tidal volume of 10 ml/kg bodyweight. Tissue elastance was repetitively measured after a recruitment maneuver to investigate the degree of distal airspace instability. The right lung was subjected to bronchoalveolar lavage (BAL), the left lung was fixed for design-based stereology at light- and electron microscopic level. Prior to mechanical ventilation, lung tissue elastance did not differ. During mechanical ventilation tissue elastance increased in bleomycin-injured lungs ventilated with PEEP = 1 cmH2O but remained stable in all other groups. Measurements at the conclusion of ventilation showed the largest time-dependent increase in tissue elastance after recruitment in B/PEEP1, indicating increased instability of distal airspaces. These lung mechanical findings correlated with BAL measurements including elevated BAL neutrophilic granulocytes as well as BAL protein and albumin in B/PEEP1. Moreover, the increased septal wall thickness and volume of peri-bronchiolar-vascular connective tissue in B/PEEP1 suggested aggravation of interstitial edema by ventilation in presence of microatelectases. At the electron microscopic level, the largest surface area of injured alveolar epithelial was observed in bleomycin-challenged lungs after PEEP = 1 cmH2O ventilation. After bleomycin treatment cellular markers of endoplasmic reticulum stress (p-Perk and p-EIF-2α) were positive within the septal wall and ventilation with PEEP = 1 cmH2O ventilation increased the surface area stained positively for p-EIF-2α. In conclusion, hidden microatelectases are linked with an increased pulmonary vulnerability for mechanical ventilation characterized by an aggravation of epithelial injury.